2007
DOI: 10.1186/gb-2007-8-11-r243
|View full text |Cite
|
Sign up to set email alerts
|

The multiple sex chromosomes of platypus and echidna are not completely identical and several share homology with the avian Z

Abstract: Echidna sex chromosomes

A comparative study of the karyotype of the short-beaked echidna shows that monotremes appear to have a unique XY sex chromosome system that shares some homology with the avian Z.

Abstract Background: Sex-determining systems have evolved independently in vertebrates. Placental mammals and marsupials have an XY system, birds have a ZW system. Reptiles and amphibians have different systems, including temperature-dependent sex determination, and XY and ZW systems that differ in orig…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 33 publications
(45 reference statements)
4
121
1
2
Order By: Relevance
“…One of the candidate avian sex determination genes, DMRT1, is localized on chromosome X5 in platypus. In human, the FEM1C gene is localized on human 5q22.3, close to the DMXL1 locus (5q23.1; Rens et al 2007). FEM1C and DMXL1 have remained in a syntenic block during mammalian and avian evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the candidate avian sex determination genes, DMRT1, is localized on chromosome X5 in platypus. In human, the FEM1C gene is localized on human 5q22.3, close to the DMXL1 locus (5q23.1; Rens et al 2007). FEM1C and DMXL1 have remained in a syntenic block during mammalian and avian evolution.…”
Section: Discussionmentioning
confidence: 99%
“…FEM1C and DMXL1 have remained in a syntenic block during mammalian and avian evolution. The DMXL1 gene is on platypus chromosome X5 near DMRT1 (Rens et al 2007), but FEM1C is not found in the platypus genome database (http://www.ensembl.org). Although both DMRT1 and FEM1C relate to the sex determination in fly and nematode, their role in birds and platypus are unknown even though they are situated on the sex chromosomes where a testis-determining role could be favored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other monotreme family, the echidnas, also have a sex chromosome chain but it consists of only nine elements, with the tiny terminal Y 5 fused onto another Y 55. Chromosome painting and gene mapping shows that four of the five XY pairs in the echidna chain are the same, but the fifth is represented by an autosome in platypus.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionmentioning
confidence: 99%
“…In any case, more robust testing of the hypotheses of the ancestral sex determination and on the evolution of sex-determining mechanisms in amniotes is largely precluded by our very limited knowledge about the homology of sex chromosomes and sex-determining genes among particular groups. The homology of sex chromosomes can be inferred from the knowledge of the gene content of sex chromosomes; however, it has been identified in only a few amniote lineages such as viviparous mammals (see, for example, Kohn et al, 2004) and monotremes (see, for example, Rens et al, 2007), birds (see, for example, Zhou et al, 2014), several turtle species (see, for example, Kawagoshi et al, 2012Kawagoshi et al, , 2014, advanced snakes (Matsubara et al, 2006;Vicoso et al, 2013;Rovatsos et al, 2015), iguanas (see, for example, Alföldi et al, 2011;Rovatsos et al, 2014a-c), a gecko (Kawai et al, 2009) and recently also a lacertid lizard (Srikulnath et al, 2014).…”
Section: Introductionmentioning
confidence: 99%